Підготовка бакалаврів технічних спеціальностей до роботи з інформацією в умовах освітнього процесу - Горбенко, Є. О. (ХНУРЕ, 2025)
This paper argues that information culture is crucial for electronics professionals due to the field's rapid evolution and vast data. The study highlights gaps in current higher education regarding information competence and asserts that information culture, including critical thinking and ethical information use, is essential for success in today's digital world. The paper concludes that universities must prioritize both technical skills and information culture development for graduates in electronics.
Keywords: підготовка бакалаврів; освітній процес